The Influence of Interpersonal Communication on Nomophobia in Married Couples - Dalimunthe, Merry; Lyona, Annisa; Negara, Atikah Nuzuli Chari; Ni’matuzahroh, Ni’matuzahroh (World Psychology, 2024)
The term used to describe an individual's dependence on smartphones is called no-mobile phone phobia (nomophobia), which refers to the fear of being disconnected from the digital world. One of the causes of nomophobia is the high need for communication. Individuals who spend a lot of time on virtual communication have a reason to escape from real-life social relationships. Individuals who fail to develop interpersonal intelligence will experience obstacles in their social lives. This study aims to explore the influence of interpersonal communication on nomophobia among married couples. The research design used is a non-experimental quantitative correlational design. The research instruments used are the NMP-Q Likert scale and the MCI scale. The study involves a total of 39 subjects. The analysis results show that 69.5% of the respondents experience a moderate level of nomophobia, while 35.9% experience a high level of nomophobia. A positive influence between interpersonal communication and nomophobia among married couples is found, thus rejecting the hypothesis.